The role of enhanced plantar-surface sensory feedback on lower limb EMG during planned gait termination. (3rd April 2021) - Robb, Kelly A.; Hyde, Jordan D.; Perry, Stephen D.
Abstract: Purpose/aim of the study : Generation of smooth movement relies on the central nervous system (CNS) having information from the visual, vestibular and somatosensory systems to effectively execute motor behaviour. Recently, cutaneous afferent inputs have been linked to lower leg motorneuron pools, resulting in a growing interest of adding texture to the plantar foot sole interface as a novel method to facilitate cutaneous feedback. The aim of this study was to characterize the changes in magnitude and temporal organization of muscle activity, and to investigate motor output changes from enhanced tactile feedback during perturbed gait termination. Materials and methods: Thirty young adults experienced an unpredictable platform perturbation when completing planned gait termination. The study manipulated two experimental variables: 1) direction of platform tilt (anterior, posterior, medial, lateral), and 2) foot sensory facilitation (non-facilitated, facilitated). Upper and lower leg EMG onset, cessation time and integrated EMG (iEMG) were measured in addition to common gait parameters (walking velocity, step length, step width). Results: Gait termination over a textured surface resulted in significantly earlier upper leg EMG onset times and modified iEMG of rectus femoris, vastus medialis and biceps femoris muscles. Conclusions: Results of this study suggest that the addition of cutaneous feedback under the plantar-surface of the foot increases the ability to generate an earlier muscle response, consequently improving response ability to an unexpected perturbation. Secondly, enhanced tactile feedback appears to inform the CNS of the magnitude of the threat to the balance control system, providing additional insight into how the CNS uses enhanced tactile feedback during a gait termination task.